"A saúde mental me ensinou mais do que eu a ela”: da formação do farmacêutico à sua atuação no campo da saúde mental - Lopes, Nadja Mara de Sousa (2017)
Professional training in the field of health allows the individual to acquire and develop scientific, technical and operational knowledge related to the production of goods and services, in addition to training him/her for work. This thesis aimed to understand the influence of the pharmacist’s training process on the work in the field of Mental Health within the context of SUS. From a macro perspective, a quantitative approach was adopted to describe and analyze the quality of Brazilian Pharmacy schools with emphasis on the quality indicators proposed by the MEC. In-depth knowledge of how the training process in one of these institutions isdeveloped until the performance in the field of mental health was obtained using a qualitative approach. Interviews were conducted with pharmacists and teachers, with observations of academic activities and focus groups with students. The research was carried out at the Federal University of Ceará between 2014 and 2017. Participants were nine pharmacists, 12 teachers and five undergraduate students. The following techniques were used to collect the information: Semi-structured interview; Focus group and Field journal. The analytical process was based on an analysis that articulated the hermeneutics and the dialectics, starting from Minayo’s interpretative trajectory (ordering, classification and final analysis), through an analyzer (flow chart) guided by Assis and Jorge (2010). The study complied with the ethical precepts of Resolution 466/2012 of the National Health Council. The findings revealed that the quality of pharmacy teaching tends to be central (grade 3), which is satisfactory. The pharmacy schools of public institutions have better quality. Specifically, the pharmacy school of UFC provides a general education, but it still has difficulties in training for work in several fields, such as in the field of mental health. The graduates who worked in this field felt insecure due to the lack of internships or any discussion about this field in the classroom. There was a change in the behavior of those who worked in mental health for seeking knowledge and participating in activities in an interdisciplinary way. The teachers knew little about the field, but the knowledge of Pharmacology, Pharmacoepidemiology, Clinical Pharmacy and Pharmaceutical Care were important for the integration process.